2014
DOI: 10.1111/bdi.12236
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological performance of patients with soft bipolar spectrum disorders

Abstract: Our data suggest that patients with SBP differ from patients with UP not only in external validators (e.g., family history of bipolar disorder) and hypomanic symptoms, but also in neuropsychological performance and that the profiles of cognitive functioning were different across bipolar I disorder and 'bipolar II spectrum' that subsumes bipolar II disorder and SBP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
11
1
Order By: Relevance
“…Comorbid borderline personality and a rapid disappearance of depressive symptoms are also seen as indicators of soft BD-II in recurrent depressive disorder patients similar to that reported from other regions of the World (Akiskal et al, 1995;Henry et al, 1999;Utsumi et al, 2006). A recent study from this region found that 'soft' bipolar patients fare well in working memory and processing speed when compared to the BD-I and BD-II patients (Lin et al, 2015). The study furthers our understanding of BD that the 'soft' bipolar individuals could represent a different endophenotype in bipolar spectrum disorders.…”
Section: Prodrome and Early Stages Of Bipolar Disordersupporting
confidence: 81%
“…Comorbid borderline personality and a rapid disappearance of depressive symptoms are also seen as indicators of soft BD-II in recurrent depressive disorder patients similar to that reported from other regions of the World (Akiskal et al, 1995;Henry et al, 1999;Utsumi et al, 2006). A recent study from this region found that 'soft' bipolar patients fare well in working memory and processing speed when compared to the BD-I and BD-II patients (Lin et al, 2015). The study furthers our understanding of BD that the 'soft' bipolar individuals could represent a different endophenotype in bipolar spectrum disorders.…”
Section: Prodrome and Early Stages Of Bipolar Disordersupporting
confidence: 81%
“…First, we give a more detailed description of all of the cognitive tasks and domains used in each of these studies (Table 2), and then we present an in depth review of the most relevant domains ( Table 3). 23 9 BDI 84/25% BDII No comorbidity controlled for 64% of overall patient group but no mention of difference between groups Aminoff et al 1 14 Not mentioned No comorbidity controlled for AP not mentioned Sparding 24 12 73%v7% No comorbidity controlled for AP not mentioned Lin et al 25 12 Next, we present accounts of each cognitive domain in the Figures 2-7 to give a more in depth review and clear answer as to whether (i) neurocognitive dysfunction in BP-II is similar to BP-I in each cognitive domain and (ii) whether these deficits exist in subsyndromal disorders SBP. Due to the limited amount of studies and to provide a more transparent account of the neuropsychological profile of (SBP), we have divided the results as follows: (i) comparison of neuropsychological functioning between BP-I and BP-II and (ii) neuropsychological functioning in SBP.…”
Section: Resultsmentioning
confidence: 99%
“…No data on these variables are available for the subgroup of subjects achieving remission after follow-up. d Only the data corresponding to 'strict MDD' were included to estimate effect sizes from the study by Lin et al [49].…”
Section: Discussionmentioning
confidence: 99%